2010
DOI: 10.1080/13588265.2010.484194
|View full text |Cite
|
Sign up to set email alerts
|

On a new crush trigger for energy absorption of composite tubes

Abstract: A new crush trigger, called crown trigger, is introduced at one end of carbon-fibre-reinforced polymer circular tubes. Quasistatic compression tests are performed on the tubes to investigate their energy absorption characteristics. It is observed that all tubes are crushed in a brittle fracturing mode. Both crown trigger and bevel trigger can effectively control the position of crushing initiation, reduce the peak load and increase the crushing stability. It is also found that the tube wall of each specimen is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Huang et al [26] observed that unconstrained 0 degree plies sustained little damage except splitting along the fibre direction, while the 90 degree plies formed thin strands between the sandwiching 0 degree plies in quasi-static crushing of chamfered cylinders. The higher resin volume fraction in this material caused it to be less fragmented overall in comparison with the present study.…”
Section: Data Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al [26] observed that unconstrained 0 degree plies sustained little damage except splitting along the fibre direction, while the 90 degree plies formed thin strands between the sandwiching 0 degree plies in quasi-static crushing of chamfered cylinders. The higher resin volume fraction in this material caused it to be less fragmented overall in comparison with the present study.…”
Section: Data Reliabilitymentioning
confidence: 99%
“…A circular cross-section also avoids stress concentrations, which leads to a more progressive and localised damage progression [19], resulting in a higher energy absorption in comparison with a square or rectangular cross-section. The triangular tulip trigger can achieve a higher steady-state crush load [19] in contrast to hourglass [20], crown and chamfer [26] triggers, leading to increased energy absorption. The increased length of the trigger region helps to spread the force spike in the initial stage of impact and reduce the peak transmitted force.…”
Section: Specimen Designmentioning
confidence: 99%
“…For the excellent interlaminate mechanical property, 3D-textile braiding [14][15][16] and multiaxial warp knitted [17] were studied as a reinforcement form aiming to an enhanced energy absorption capacity. The influences of crush trigger [18,19] and off-axis loads [20] on energy absorption tests were also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The crush takes place progressively, and consequently the energy can be dissipated with high energy absorption, long stroke and crushing stability along a large plastic deformation process (Reid, 1993) . The thinwalled circular tubes under axial impact loading could absorb the energy with different mechanisms such as splitting (Niknejad et al, 2013), extrusion (Galib et al, 2006), expansion (Salehghaffari et al, 2010), trigger (Huang and Wang, 2010), inversion (Guist and Marble, 1966;Rosa et al, 2003;Luo et al, 2007;Gupta, 2014;andQiu et al, 2014), stiffeners (lateral or longitudinal ) (Zhang and Suzuki, 2007), metal cutting (Jin and Altenhof, 2011). During the progressive crushing under axial compression, different types of deformation modes such as an axisymmetric (concertina) mode, nonsymmetric (diamond) mode, mixed mode or global Euler buckling mode, could happen depending on the geometric parameters of the tube (length, diameter and thickness),material properties and boundary conditions (Andrews et al, 1983;Abramowicz and Jones, 1984).…”
Section: Introductionmentioning
confidence: 99%